2001
DOI: 10.1097/00004691-200111000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of EEG in Alzheimer Disease

Abstract: The aim of our study was to analyze EEG changes in patients with Alzheimer disease (AD) and to determine how closely EEG reflects the progression of mental impairment in people with AD. Ninety-five patients with probable AD according to National Institute of Neurological and Communicative Disorders and Stroke/Alzheimer's Disease and Related Disorders Association criteria treated in our Clinic for Memory Disorders were selected for this study. Patients were divided into three subgroups with mild, marked, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 14 publications
6
33
0
Order By: Relevance
“…In our study a substantial proportion of patients with AD (28%) showed no EEG abnormalities, in accordance with previous studies [9,11,12,13,24]. The neuropsychological test scores were relatively least impaired in this group of patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study a substantial proportion of patients with AD (28%) showed no EEG abnormalities, in accordance with previous studies [9,11,12,13,24]. The neuropsychological test scores were relatively least impaired in this group of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with only diffuse abnormalities were in general most severely impaired on neuropsychological testing and slightly more impaired on global cognition (MMSE = 21 ± 5), in line with former studies [13,15,16]. The present study extends these findings, as we took into account performance on specific neuropsychological tests.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The main EEG abnormalities in AD are slowing of alpha activity and increases in theta and delta activities, and these changes correspond well with the severity of AD [13,14,15]. Quantitative data from EEG recordings are generated by use of computerized analysis [16], and quantitative EEG (qEEG) parameters have repeatedly shown good discriminatory power between different dementia disorders and healthy aging in a number of clinical studies [17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%